Bread as Food and Medicament in Oribasius’ Writings - Kokoszko, Maciej; Jagusiak, Krzysztof; Dybała, Jolanta (Studia Ceranea, 2016)
Treatises left by Oribasius (first and foremost his Collectiones medicae and Eclogae medicamentorum) preserve a vast body of information on the varieties of bread eaten in late antiquity, characterise them from the point of view of dietetics, list medical conditions in which a given variety is especially beneficial, and name medical preparations which include the product. The present study elaborates on Oribasius’ dietetic knowledge and his input into the development of dietetic discourse (namely his influence on Byzantine dietetic doctrine), determines Oribasius’ main information sources on bread, characterises bread as food, lists varieties which were thought to be used by physicians and explains reasons for the preferences, and finally exemplifies cures and medical preparations which include bread.